Midazolam frente a dexmedetomidina en sedacción en cirugía ginecológica en el Hospital Nacional Arzobispo Loayza 2015 - Siu Wong, Carlos Gustavo (2016)
Objective: To determine the level of sedation and respiratory depression between midazolam and dexmedetomidine. Material and Methods: quantitative, observational, analytic, prospective study, experimental and inferential. Results: Sedation with midazolam was higher than the dexmedetomidine, with respect to respiratory depression using ANOVA test sp02 levels with midazolam were lower than the dexmedetomidine, p = 0.010 ,frequency variable and in amplexation variable with dexmedetomidine was decreased statistically significant with p < 0.001. Conclusions: Dexmedetomidine has sedative effects, without producing respiratory depression; the midazolam has a good sedative effect with some level of respiratory.